Youth Calendar in the Context of Traditional Culture of Ukrainians - Chebanyuk, О.Yu. (Слов’янський світ, 2014)
У статті розглянуто інваріантну модель українського молодіжного календаря, ритуали й фольклорні твори у виконанні молоді протягом обрядового річного циклу українців. На практиці вони існують у численних формах і діалектних варіантах. Корпус усіх діалектних форм молодіжного календаря на всіх українських етнічних територіях є органічною складовою українського традиційного календаря. В статье рассматривается инвариантная модель украинского молодежного календаря, ритуалы и фольклорные произведения в исполнении молодежи на протяжении обрядового годового цикла украинцев. На практике они существуют в многочисленных формах и диалектных вариантах. Корпус всех диалектных форм молодежного календаря на всех украинских этнических территориях – это органическая часть украинского традиционного календаря. This article covers invariant model of Ukrainian youth folk calendar, major folklore genres that accompany ritual and ceremonial actions. In practice, they all function in various dialect forms and variants. The range of all the dialect forms from all Ukrainian territories form youth calendar as an organic part of the general folk calendar. Th e anthropocentric view of the world is typical for youth calendar and is an element of Ukrainian traditional culture in its entirety.